New records of Lasiocampidae (Lepidoptera) from Zanzibar Island with taxonomic notes and description of one new species of Odontopacha Aurivillius, 1909 - Prozorov, Alexey M.; Prozorova, Tatiana A.; Spitsyn, Vitaly M.; Spitsyna, Elizaveta A.; Kondakov, Alexander V.; Soboleva, Alena A.; Volkova, Julia S.; Yakovlev, Roman V.; Saldaitis, Aidas; Sulak, Harald E.; Revay, Edita E.; Müller, Günter C. (Zootaxa, 2023)
Seven genera and seven species of Lasiocampidae are newly recorded from the Zanzibar Island (Unguja): Bombycopsis C. & R. Felder, 1874 with Bombycopsis nigrovittata Aurivillius, 1927; Pallastica Zolotuhin & Gurkovich, 2009 with an unidentified species; Dollmania Tams, 1930 with an unidentified species; Mallocampa Aurivillius, 1902 with Mallocampa leighi Aurivillius, 1922; Eucraera Tams, 1930 with Eucraera witti Prozorov, 2016; Philotherma Möschler, 1887 with Philotherma montibia Strand, 1912; and Odontopacha Aurivillius, 1909 with Odontopacha fenestrata Aurivillius, 1909. The species are followed with taxonomic notes updating the status and distribution of the taxa. Bombycopsis nigrovittata is shown to have the maximum p-distance of 0.3% in cytochrome c oxidase I from Bombycopsis pallida Joannou & Krüger, 2009. Two specimens of Pallastica sp. from Zanzibar are different in wing coloration but identical genetically, both are 0.8–1.2% far from sequenced specimens collected in southern Malawi and eastern Zimbabwe and altogether 3.0–3.8% far from the Zambian and Malawian populations considered to be Pallastica pallens (Bethune-Baker, 1908). The barcoding revealed two distinct lineages of Dollmania in Tanzania with a p-distance of 3.5–3.7% between them, neither can be attributed to either Dollmania marwitzi (Strand, 1913) or Dollmania reussi (Strand, 1913) until the primary types or fresh topotypes are sequenced. The species Ph. montibia is taken out from the synonymy to Philotherma rosa (Druce, 1887) and is stated to be a bona species because of the difference in wing pattern and p-distance of 5.7–5.9%. A new species of the genus Odontopacha – Odontopacha dargei sp. n. – is described from southern Kenya and northern Tanzania where it occurs sympatrically with O. fenestrata. It differs from O. fenestrata by the paler coloration with the spotted external fascia on both wings and a p-distance of 3.04–3.65%. Lectotypes for D. marwitzi and Ph. montibia are established. Mallocampa leighi is recorded from Tanzania for the first time. Females of Chrysopsyche lutulenta Tams, 1923 earlier recorded from Zanzibar Island are figured and the species is recorded from DRC for the first time.